Los inicios del cine documental y la antropología - Martínez Montiel, Jerónimo (Cuadernos de Documentación Multimedia, 2009)
Nowadays, documentary films of the silent era (1895-1927) gain value from an anthropologic point of view. In the birth of this genre, documentary films were produced to explore commercial interests and divulgative purposes but today there are scarce possibilities for it to be commercialized or screened. In spite of the fact that documentary films were not created by specialists in anthropology, it is the study of its contents what may make us focus our attention on it today, technical issues aside. No doubt that documentary films stem as one of the best tools we have to outline the human being of the beginning of twentieth century.